Strategic Talent Management in the Digital Era: Its Impact on Organizational Performance and Competitive Advantage - Darmawaty Syam; Victor P. K. Lengkong; Rita N. Taroreh; Christoffel M. O. Mintardjo (Maneggio, 2026)
The digital transformation era has fundamentally reshaped the strategic landscape of talent management, compelling organizations to rethink how human capital is identified, developed, and retained. This study examines the relationship between Strategic Talent Management (STM) in the digital era and its impact on organizational performance and competitive advantage. Using a systematic literature review methodology, eighteen peer-reviewed articles published between 2019 and 2026 were analyzed. The findings reveal that digital-era STM, characterized by AI-driven talent analytics, agile workforce ecosystems, continuous digital learning, and data-informed performance management, significantly enhances organizational performance metrics including productivity, innovation output, and financial results. Furthermore, organizations that strategically align talent management practices with digital transformation imperatives achieve sustainable competitive advantage through the accumulation of rare, valuable, and inimitable human capital. The study proposes a comprehensive conceptual framework integrating digital talent acquisition, development, retention, and knowledge management as interconnected pillars of organizational competitiveness. Key moderating factors identified include organizational ambidexterity, digital leadership capability, and total quality management integration. Practical implications are provided for organizational leaders and HR strategists navigating the complexities of talent management in an increasingly digitized global economy.